2018
DOI: 10.1016/j.nuclphysa.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Lindblad and Bloch equations for conversion of a neutron into an antineutron

Abstract: We propose a new approach based on the Lindblad and Bloch equations for the density matrix to the problem of a neutron into an antineutron conversion. We consider three strategies to search for conversion: experiments with trapped neutrons, oscillations in nuclei, and quasi-free propagation. We draw a distinction between nn oscillations in which the probability that a neutron transforms into an antineutron depends on time according to the sine-square law and the non-oscillatory overdamped nn conversion. We sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…We note in passing that inside nuclei or in nuclear matter for relevant times Γt ≫ 1(Γ ∼ 10 23 s −1 ) equation (26) leads to a result which looks quaite different [6,26]…”
Section: Hitting the Wall The Time-dependent Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…We note in passing that inside nuclei or in nuclear matter for relevant times Γt ≫ 1(Γ ∼ 10 23 s −1 ) equation (26) leads to a result which looks quaite different [6,26]…”
Section: Hitting the Wall The Time-dependent Approachmentioning
confidence: 99%
“…In the correct equations the waves hitting the wall and reflected from it must be mixtures of the n andn components. For the conversion inside nuclei coupled equations have been formulated and solved using either the optical potential [20,[22][23][24][25] or the Bloch equations [6]. To our knowledge Ref.…”
Section: Reflection From the Wall: Optical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantum correlations have been studied mainly in the optical and electronic systems [7][8][9][10]. Recently such studies have been extended to high energy physics owing to the advancement in various experimental facilities, see for example [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The concept of single particle entanglement has been introduced in previous studies [25][26][27] which have also been demonstrated experimentally with single photon systems [28][29][30].…”
Section: Introductionmentioning
confidence: 99%